Tandem Decarboxylative Allylation and Fragmentation of Allyl Benzocyclobutenyl Carbonates: Access to ortho-Functionalized Aryls from Aryl Bromides - Rosa, David; Chtchemelinine, Andrei; Orellana, Arturo (Synthesis, 2012)
Allyl benzocyclobutyl carbonates yield ortho-allyl α-aryl ketones through a palladium-catalyzed decarboxylative allylation, fragmentation, and cross-coupling process.
Keywords: benzocyclobutenol; decarboxylative allylation; palladium; fragmentation; strain release